Sequencing-guided design of genetically encoded small RNAs targeting CAG repeats for selective inhibition of mutant huntingtin - Mansi A. Parasrampuria; Adam A. White; Ramadevi Chilamkurthy; Adrian A. Pater; Fatima El-Azzouzi; Katy N. Ovington; Philip J. Jensik; Keith T. Gagnon (Elsevier, 2024)
Huntington's disease (HD) is an incurable neurodegenerative disorder caused by genetic expansion of a CAG repeat sequence in one allele of the huntingtin (HTT) gene. Reducing expression of the mutant HTT (mutHTT) protein has remained a clear therapeutic goal, but reduction of wild-type HTT (wtHTT) is undesirable, as it compromises gene function and potential therapeutic efficacy. One promising allele-selective approach involves targeting the CAG repeat expansion with steric binding small RNAs bearing central mismatches. However, successful genetic encoding requires consistent placement of mismatches to the target within the small RNA guide sequence, which involves 5' processing precision by cellular enzymes. Here, we used small RNA sequencing (RNA-seq) to monitor the processing precision of a limited set of CAG repeat-targeted small RNAs expressed from multiple scaffold contexts. Small RNA-seq identified expression constructs with high-guide strand 5' processing precision and promising allele-selective inhibition of mutHTT. Transcriptome-wide mRNA-seq also identified an allele-selective small RNA with a favorable off-target profile. These results support continued investigation and optimization of genetically encoded repeat-targeted small RNAs for allele-selective HD gene therapy and underscore the value of sequencing methods to balance specificity with allele selectivity during the design and selection process.